ALDH2 Inhibition Potentiates High Glucose Stress-Induced Injury in Cultured Cardiomyocytes - Guodong Pan; Mandar Deshpande; Rajarajan A. Thandavarayan; Suresh Selvaraj Palaniyandi (Journal of Diabetes Research)
Aldehyde dehydrogenase (ALDH) gene superfamily consists of 19 isozymes. They are present in various organs and involved in metabolizing aldehydes that are biologically generated. For instance, ALDH2, a cardiac mitochondrial ALDH isozyme, is known to detoxify 4-hydroxy-2-nonenal, a reactive aldehyde produced upon lipid peroxidation in diabetic conditions. We hypothesized that inhibition of ALDH leads to the accumulation of unmetabolized 4HNE and consequently exacerbates injury in cells subjected to high glucose stress. H9C2 cardiomyocyte cell lines were pretreated with 10 μM disulfiram (DSF), an inhibitor of ALDH2 or vehicle (DMSO) for 2 hours, and then subjected to high glucose stress {33 mM D-glucose (HG) or 33 mM D-mannitol as an osmotic control (Ctrl)} for 24 hrs. The decrease in ALDH2 activity with DSF pretreatment was higher in HG group when compared to Ctrl group. Increased 4HNE adduct formation with DSF pretreatment was higher in HG group compared to Ctrl group. Pretreatment with DSF leads to potentiated HG-induced cell death in cultured H9C2 cardiomyocytes by lowering mitochondrial membrane potential. Our results indicate that ALDH2 activity is important in preventing high glucose induced cellular dysfunction.